Dialettica del fantastico. Il (mobile) confine tra noto e ignoto in Guy de Maupassant - Domenico Tanteri (Between, 2011)
Maupassant, a writer of a largely positivist background, considers the problem of the relationship between the known and the unknown and rationalistically deals with this issue in several texts, both of a narrative and a theoretical nature.